2011
DOI: 10.1111/j.1399-3046.2011.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of graft steatosis and protein‐losing enteropathy after biliary diversion in a PFIC 1 liver transplanted child

Abstract: PFIC 1 is a genetic disorder characterized by hepatic and gastrointestinal disease, often requiring LT during childhood. Extrahepatic symptoms, such as diarrhea and malabsorption, do not improve or may be aggravated after LT, as graft steatosis or steatohepatitis as consequences of the interaction between transplanted liver and native bowel. We describe a patient with PFIC 1 who presented with cholestasis in infancy, who developed intractable pruritus and liver fibrosis. The child underwent living donor LT at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 17 publications
4
64
0
Order By: Relevance
“…Posttransplant NAFLD in pediatric liver transplant recipients has been documented only in case series and reports69‐77 (Table 5). Four of the 19 children reported in these studies underwent transplantation for cirrhosis associated with nonalcoholic steatohepatitis (NASH) 69‐71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Posttransplant NAFLD in pediatric liver transplant recipients has been documented only in case series and reports69‐77 (Table 5). Four of the 19 children reported in these studies underwent transplantation for cirrhosis associated with nonalcoholic steatohepatitis (NASH) 69‐71.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve children with posttransplant NAFLD had progressive intrahepatic familial cholestasis type 1 (PFIC1); none were overweight. Instead, 11 had chronic diarrhea and malnutrition thought to be secondary to restored bile flow from the liver (with persistently abnormal intestinal reabsorption) and pancreatic insufficiency 76. NASH was resolved for 1 patient after external biliary diversion 76…”
Section: Resultsmentioning
confidence: 99%
“…Surgical techniques have included external biliary diversion versus internal biliary diversion in both the pre‐LT and post‐LT setting. As previously mentioned, Nicastro et al reported successful outcome with external biliary diversion using a jejunal loop in a post‐LT patient with improvement in diarrhea within 1 week, resolution of protein‐losing enteropathy, and dramatic reversal of steatosis at 6 months. Usui et al reported a patient who underwent an external biliary diversion with a jejunal loop at the time of re–liver transplantation.…”
Section: Discussionmentioning
confidence: 84%
“…This interesting phenomenon may have to do with faulty gut regulation of uptake of bile acids and other substances (Oude Elferink et al 2002 ;Chen et al 2004 ). Both diarrhea and hepatic steatosis after LTX may respond to biliary diversion (Nicastro et al 2012 ), that is, to directing bile from the allograft liver away from the native small bowel. Both diarrhea and hepatic steatosis after LTX may respond to biliary diversion (Nicastro et al 2012 ), that is, to directing bile from the allograft liver away from the native small bowel.…”
Section: Slco1b1/ Slco1b3mentioning
confidence: 99%